The Experience of Women with Infertility: A Synthesis of Qualitative Study - Pangzup, Saowaros; Ratinthorn, Ameporn; Kasak, Rungtip; Cananub, Porntip (Nursing Science Journal of Thailand, 2021)
Purpose: The objective of this study was to review and perform meta-synthesis of studies to study experiences, coping and care needs of infertile women. Design: This study is a systematic review and synthesis of qualitative studies by searching for studies published in January 2015 to May 2020 from the PubMed, MEDLINE, Academic Search Complete, Nursing & Allied Health Database (ProQuest), Scopus and Web of Science databases. The main search keywords were “experience”, “infertility”, “qualitative study” and “women”. Two authors independently assessed article quality, analyzed to identify themes and synthesize to obtain new meaning. Research findings: Out of 17 qualitative studies, experiences of women with infertility were found to have five issues: the nature of being infertile women, coping and managing infertility problems, negative reactions from surrounding people perceived by women, effects on relationships and health care needs. Conclusion and recommendations: Infertile women experience unseen feelings of loss, self-blame, perceived negative reactions from family and the people around them, lack adequate support from healthcare professionals, particularly in the psychological area. Therefore, families, friends and healthcare professionals are essential to providing support and empowerment for women to enable infertile women to properly overcome this suffering.